CONSTRUCTAL LAW, AND THE ALBEDO AND GLOBAL WARMING CONUNDRUM - HEITOR REIS, ANTONIO (2018)
In the current debate on global warming is under analysis whether the albedo will increase with temperature, and may thus constitute a negative feedback mechanism by increasing the amount of solar radiation reflected into space. This issue is analyzed in this paper in the light of the Constructal Law. In fact, by maximizing the overall conductivity of the processes that lead to the thermalization of the solar energy absorbed on Earth and its subsequent radiation into space at the global average temperature, it is possible to conclude that the albedo should increase with the global temperature, thus constituting a negative feedback mechanism that will help to restrain the increase of global temperature. Additionally, the value found for the rate of variation of the albedo with global surface temperature is very close to the values published in the literature, which were obtained both through satellite data and ground-based observations. Although they result from a preliminary analysis, these results are encouraging towards the implementation of the Constructal Law in the analysis of the climate system.